Low phase noise oscillator using a new planar hairpin resonator for X‐band applications. Issue 7 (26th April 2013) - Shrestha, Bhanu; Yoon, Ki‐Cheol; Lee, Jeong‐Hun
Abstract This article proposed a new high loaded quality factor (QL) hairpin resonator with a combination of a stepped impedance resonator and single split ring resonator and its application to low phase noise oscillator for X‐band applications.A new resonator has a good characteristic of S‐parameter responses. The microwave oscillator is designed at 10 GHz that exhibited a low phase noise characteristic due to the high loaded QL of the new resonator. A series feedback network is used to generate the negative resistance to make oscillation. Experimental results of the microwave oscillator show the phase noise characteristic of −103.69 dBc/Hz at 100 kHz offset with output power of 15.56 dBm. The second harmonic suppression is −32.25 dBc, which is very important in wireless communication system. The figure of merit of the fabricated oscillator is −180 dBc/Hz. © 2013 Wiley Periodicals, Inc. Microwave Opt Technol Lett 55:1508–1511, 2013; View this article online at wileyonlinelibrary.com. DOI 10.1002/mop.27608